Absolute and relative reliability of SCRuM test battery components assembled for schoolboy rugby players playing competitive rugby in low-resource settings: A pragmatic in-season test-retest approach - Matthew Chiwaridzo; Cathrine Tadyanemhandu; Nonhlanhla S. Mkumbuzi; Jermaine M Dambi; Gillian D Ferguson; Bouwien CM Smits-Engelsman (South African Sports Medicine Association, 2023)
Abstract